Finite-Time Group Consensus of Distributed Multiagent Systems Based on Competition Mechanism. (16th March 2020) - Yang, Yize; Yang, Hongyong; Liu, Fei
Abstract : With the development of communication technology, distributed cooperative controls of multiagent systems (MAS) have been applied in many fields. Based on the communication between the agents, multiple individual systems are composed of a distributed network. Since the function of the agents is different, the distributed network can be divided into many parts. For first-order/second-order dynamic MAS, group cooperation algorithms with the competition mechanism are proposed in this paper. By applying modern control theory and homogeneous theory, finite-time stabilities for the cooperation motion of dynamic MAS are analyzed. By studying the dynamic properties of agents, finite-time group consensus of distributed MAS based on directed topology is obtained. Finally, the system simulation results are given to illustrate the effectiveness of the conclusion.